2021
DOI: 10.2478/bhk-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additional load on angular parameters during gait and balance in children with hemiparesis – Cross sectional study

Abstract: Study aim: To study the effect of additional load over ankle and knee joints on angular parameters during gait and balance in children with hemiparesis. Material and methods: 10 children with hemiparesis were recruited and stratified into 2 chronological age groups: group A (4–8 years) and group B (9–12 years). Additional loads of 0.7 kg and 1.1 kg were placed on the affected and non-affected lower limb at the ankle and knee joint for group A and group B respectively. Angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the observations of Hoffman [34], patients after brain tumor surgery performed the TUG test within 5.1 s, and their recorded test time was very similar to the time obtained in the group of healthy children. On the other hand, in the group of children after stroke, Berkner et al [35] observed a slower gait, shorter stride and increased walking cadence which results from difficulties with tasks requiring greater coordination [36,37]. A study by Rahman et al [38] in patients after TBI with the TUG test demonstrated a significantly reduced walking speed (11.5 s) and frequency of steps, when compared to healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…In the observations of Hoffman [34], patients after brain tumor surgery performed the TUG test within 5.1 s, and their recorded test time was very similar to the time obtained in the group of healthy children. On the other hand, in the group of children after stroke, Berkner et al [35] observed a slower gait, shorter stride and increased walking cadence which results from difficulties with tasks requiring greater coordination [36,37]. A study by Rahman et al [38] in patients after TBI with the TUG test demonstrated a significantly reduced walking speed (11.5 s) and frequency of steps, when compared to healthy children.…”
Section: Discussionmentioning
confidence: 99%